Guardados da Memória: matas do sertão de baixo, longos serões do campo e fidalgos e vaqueiros - Araújo, Carla de Quadros (2008)
This dissertation is an analytical study comparing three works: Matas do Sertão de Baixo (The Woods of the Lower Sertão**) by Isaías Alves, Longos serões do campo (Working Overtime in the Countryside) by Anna Ribeiro Góes de Bittencourt and Fidalgos e vaqueiros (Noblemen and Cowboys) by Eurico Alves Boaventura. These authors are all from the state of Bahia (North East Brazil) and all of these works use the same classificatory rubric. Through the analysis of the above works as well as by cross-referencing several theoretical studies, it has become evident that the works have a memorialist nature and make an important contribution to social memory, especially to the social memory of Bahia between the seventeenth and twentieth centuries. The way in which the memorial universes are constructed through a pluralistic narrative contrived in the figure of a narrator-author-character is also discussed. These observations constitute an inter- textual dailogue which reveals the confluence between the History/Literature/Memories presented in memorialist discourse. The authors create/recreate facts from memories seemingly forgotten and which are brought to life in an effort to recuperate regional memoriam. These memories are captured in richly stylistic language that extends throughout the works vividly describing different themes, intoned in distinct images. We also try to define themes which approximate and distance the authors, not with classificatory aims, but to try to enhance the quality of the comparisons being made. The interchange between History/Literature/Memories taking place does not represent a dichotomy, but the presentation of different viewpoints and pluralistic readings of works which bring, within their dense structures, valuable memories.